Advances in intelligent data analysis XV : 15th International Symposium, IDA 2016, Stockholm, Sweden, October 13-15, 2016, Proceedings /: 15th International Symposium, IDA 2016, Stockholm, Sweden, October 13-15, 2016, Proceedings. (2016) - Unknown
No abstract available